The conditions and tendencies of the development of the tax system in agriculture of the EAEC countries - Баяндин, М.; Нарынбаева, A. (Journal of Economic Research & Business Administration, 2017)
The article views the peculiarities of applying the special tax regimes in the agricultural production of the EAEC member-countries, the main challenges and trends in the development of tax policy, the analysis of the main types of taxes and tax rates for agricultural producers has been conducted. It is indicated that under current conditions some changes are taking place in the processes of development and implementation of legislation in respect of taxes due to the harmonization of taxation. The measures to promote the agricultural commodity producers’ activity have been identified. The study showed that the full unification of basic tax rates in the states - members of the EAEC is not observed yet, because the size of tax rates and collection depends on the level of economic development, as well as the fiscal policy pursued by each of the states and the course of reforms in this area. The functioning of the economic mechanism in the field of taxation and the results of the comparative analysis of the tax system of the agricultural commodity producers of the EAEC countries allow us to offer to take the path of unification based on the experience of each of the EAEC participating country in the development of inter-state tax system. Solving these problems will contribute to the production growth and diversification of the EAEC economies.